HIV replication in conjunction with granzyme B production by CCR5+ memory CD4 T cells: implications for bystander cell and tissue pathologies - Couturier, Jacob (2014)
Granzyme B (GrzB) is expressed by activated T cells and mediates cellular apoptosis. GrzB also acts as an extracellular protease involved in tissue degradation. We hypothesized that GrzB production from activated memory CD4 T cells may be associated with HIV pathogenesis. We found that stimulated memory CD4 T cells (via costimulation, cytokines, and TLR ligands) concomitantly produced GrzB and HIV. Both GrzB and HIV expression were mainly restricted to CCR5-expressing memory CD4+CD45RO+ T cells, including Th1 and Th17 subsets. Activated memory CD4 T cells also mediated tissue damage, such as disruption of intestinal epithelial monolayers. In non-human primates, CD4 T cells of rhesus macaques (pathogenic SIV hosts) expressed higher GrzB compared to African green monkeys (non-pathogenic SIV hosts). These results suggest that GrzB from CCR5+ memory CD4 T cells may have a role in cellular and tissue pathologies during HIV infection.